Identification of Reclamation Area in Ancol of North Jakarta Using Resistivity Method - Dino Gunawan Pryambodo; Joko Prihantono; Syaiful Imam; Abdurrahman Wafi; Panganggit Sasmito (Jurnal Segara, 2021)
The coastal reclamation area is an expansion of coastal areas through technical engineering to develop new land areas. Identification of the reclamation area can be performed by detecting subsurface imaging using the resistivity method. This study used a multi-electrode (multichannel) resistivity imaging method. The resistivity imaging results show a good response of subsurface resistivity and successfully identified reclamation area with low resistivity <27.8 Ωm in almost the study area. Its depth varies from 4 meters to 30 meters. The reclamation results are composed of loose rock that has not been fully compacted, so it has not been well consolidated. As a result, it will experience land subsidence if overload.